(untitled) (Philology, 2023)
The article analyzes the concept of “soul” in the work of one of the founders of the Sufi Turkic branch of Islam Khoja Ahmed Yassavi “Divani Hikmet”. In the philosophy of the Sufis, the soul of a person emanating from the Creator occupies a special place. According to the ideology and practice given in Yassawi’s “Hikmets”, the knowledge of the path to God involves the following stages: following the codes of Islamic law (Sharia); following the Sufi teachings (tarikat); approaching Allah (haqiqah); knowledge of religion (ma’arifat). These stages, which contribute to the purification of the soul and the approach to Allah, show that the violation of this sequence cannot lead to the achievement of “Haqiqat” (“Truth”). Each of the seven stages of the development of the soul, according to the Turkic Sufi, personifies the transition to a new state, which serves to purify it from worldly vices. The motivation for this transformation is an unbridled love for the Creator, which is expressed in the service of good. The leading force on the path to Truth is love. In the name of love for the Creator, a person must undergo ascetic trials in order to deserve union with Him. It is Allah who shows the way to reach the goal. To do this, one must accept death as the birth of a new life.